2021
DOI: 10.1021/acsestwater.1c00213
|View full text |Cite
|
Sign up to set email alerts
|

Transformative Catalysis Purifies Municipal Wastewater of Micropollutants

Abstract: We describe the use of TAML/peroxide to reduce micropollutants (MPs) in Tucson, AZ, secondary municipal wastewater. The laboratory studies establish simple-to-apply MP abatements rivaling ozone in technical performance. The approach rests on the latest-generation TAML catalyst, 2, currently the highest-technical performance H 2 O 2 activator across both chemistry and biology. Thirty-eight MPs were examined with five 2/H 2 O 2 treatments (50 nM 2 with 22.4 ppm H 2 O 2 , 100 nM 2 with 11.2 ppm H 2 O 2 , 100 nM 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
(73 reference statements)
1
11
0
Order By: Relevance
“…These [Fe(TAML)] − species are oxidised by hydrogen peroxide to form extremely reactive iron(V)-oxo species (see Scheme 2) which, in turn, are capable of oxidising the strong C-H and C-C bonds in organic micropollutants. [10][11][12] Selectivity might also be engineered into the high-valent metal catalysts, such as the [Fe(O) (TAML)] − system described here, to enable more targeted removal of micropollutants in the presence of far greater Scheme 1 Top: Reactions of phenol, with chlorine disinfectant (ClOH/ClO − ). Below: One of the many pathways that generate chloroform from the reactions of phenol with chlorine disinfectant (ClOH), showing the consumption of at least four equivalents of chlorine for each molecule of chloroform produced.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…These [Fe(TAML)] − species are oxidised by hydrogen peroxide to form extremely reactive iron(V)-oxo species (see Scheme 2) which, in turn, are capable of oxidising the strong C-H and C-C bonds in organic micropollutants. [10][11][12] Selectivity might also be engineered into the high-valent metal catalysts, such as the [Fe(O) (TAML)] − system described here, to enable more targeted removal of micropollutants in the presence of far greater Scheme 1 Top: Reactions of phenol, with chlorine disinfectant (ClOH/ClO − ). Below: One of the many pathways that generate chloroform from the reactions of phenol with chlorine disinfectant (ClOH), showing the consumption of at least four equivalents of chlorine for each molecule of chloroform produced.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] We have recently demonstrated that hydrophobic disinfection byproducts can be quantified in real time using a scaled down experimental laboratory reactor interfaced directly to a membrane inlet mass spectrometer, with detection limits for CHCl 3 and CHBrCl 2 trihalomethanes at 2 ppb (16 and 12 nM, respectively), 20 well below the guidelines for safe drinking water set by the WHO (300 and 60 ppb for CHCl 3 and CHBrCl 2 , respectively). 2 Previous quantification studies at realistic concentrations of micropollutants have largely relied on far less sensitive 1 H NMR or UV-vis absorbance spectroscopies, 10,15 or more sensitive chromatographic techniques (e.g., UHPLC), [10][11][12] which lose time resolution during sample preparation and analyte residence time (tens of minutes to hours). In this work, we follow the formation of disinfection byproducts on hypochlorite treatment of Danish tap water, laced with phenol (16 μM, 1.5 ppm) as a model micropollutant, and demonstrate that even very small concentrations of an [Fe(TAML)] − catalyst (tens of nM, ppb) result in rapid removal of phenol without halophenol or trihalomethane accumulation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is considerable interest in sustainable new technologies that avoid disinfection byproducts. Two conventional alternatives, ozonation and UV radiation, have their own limitations. While little to no harm to humans and aquatic life is caused by UV-radiation-based processes, they are less cost-effective than chlorination . Alternatively, bacteria and viruses are more effectively destroyed by ozone.…”
Section: Introductionmentioning
confidence: 99%